PERAN SARAK OPAT DALAM PERKAWINAN ADAT GAYO DI KABUPATEN ACEH TENGAH - Yanti, Rahma; Manfarisyah, manfarisyah; Malahayati, Malahayati (Fakultas Hukum Universitas Malikussaleh, 2024)
AbstractThis research aims to determine the role of sarak opat in Gayo traditional marriages in Central Aceh district. The research method used is normative juridical, analytical descriptive. Furthermore, the nature of this research is descriptive qualitative by explaining and answering in detail the problems to be studied. The results of the discussion show that sarak opat is a customary institution in Gayo society so that those who violate customs will be subject to customary sanctions, just as in Gayo traditional marriages it is prohibited to carry out patrilineal marriages because in one party there is still one structure. Therefore, traditional institutions impose sanctions on perpetrators based on the cause of the perpetrator's actions, including heavy and light sanctions. Keywords: The Role of Sarak Opat, Imposing Customary Sanctions, Gayo Traditional Marriage. AbstrakPenelitian ini bertujuan untuk mengetahui peran sarak opat dalam perkawinan adat Gayo dikabupaten Aceh Tengah. Metode penelitian yang digunakan adalah yuridis normatif, deskritif analitis. Selanjutnya sifat penelitian ini adalah deskriptif kualitatif dengan menjelaskan dan menjawab secara rinci permasalahan yang akan diteliti. Hasil pembahasan menunjukan bahwa sarak opat adalah lembaga adat dalam masyarakat Gayo yang dapat menjatuhkan sanksi bagi pelaku yang melarangar adat, dilihat dari sebab perbuatan pelaku ada sanksi berat dan ringan. Kata Kunci: Peran Sarak Opat, Penjatuhan Sanksi Adat, Perkawinan Adat Gayo.